Hubungan Antara Self Efficacy Dengan Manajemen Diri Pada Penderita Hipertensi Di Masyarakat RW 07 Desa Genengan Kabupaten Malang - Permatasari, Intan; Lumadi, Sih Ageng; Raharjo, Puguh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Hypertension management heavily depends on patients self-efficacy and self-management behaviors. Self-efficacy, defined as one’s belief in their ability to perform specific tasks, plays a critical role in motivating hypertensive patients to manage their condition effectively. Poor management of hypertension can lead to severe complications such as heart attacks, strokes, and kidney failure. Therefore, understanding the relationship between self-efficacy and self-management is essential to improving health outcomes in hypertensive populations. Objective: This study aimed to explore the relationship between self-efficacy and self-management among hypertensive patients in RW 07, Genengan Village, Pakisaji District, Malang Regency. Methods: A quantitative correlational study was conducted involving 38 hypertensive respondents. Self-efficacy was measured using the General Perceived Self-Efficacy Scale (scores 10–30), categorized into poor (10–20) and good (21–30). Self-management was assessed through the Hypertension Self-Management Behavior Questionnaire (HSMBQ) with scores ranging from 25 to 125, classified as poor, moderate, or good management. Data were collected through questionnaires and analyzed using Spearman Rank correlation with SPSS version 23 at a significance level of α < 0.05. Results: Findings revealed that 65.8% of respondents possessed good self-efficacy, while 34.2% had poor self-efficacy. Regarding self-management, 47.4% exhibited moderate management behaviors, 28.9% poor, and 23.7% good. Most participants were female (79%) and married (100%), with a majority having family history of hypertension (63%) and long disease duration of 10–20 years (79%). The use of antihypertensive medication, primarily Amlodipin, was common. Self-efficacy showed a significant positive correlation with self-management. Conclusion: Higher self-efficacy is associated with better self-management among hypertensive patients. Interventions aimed at enhancing self-efficacy may improve patients’ ability to manage hypertension effectively, potentially reducing complications and improving quality of life.